Hyperbaric oxygen preserves neurotrophic activity of carbon monoxide-exposed astrocytes. (24th June 2016) - Jurič, Damijana M.; Šuput, Dušan; Brvar, Miran
Highlights: CO in high doses suppresses neurotrophic activity of astrocytes. Hyperbaric, but not normobaric, oxygen restores astrocytic synthesis of neurotrophins. Hyperbaric oxygen has the highest beneficial effect at 1–5 h after CO exposure. Abstract: In astrocytes, carbon monoxide (CO) poisoning causes oxidative stress and mitochondrial dysfunction accompanied by caspase and calpain activation. Impairment in astrocyte function can be time-dependently reduced by hyperbaric (3 bar) oxygen (HBO). Due to the central role of astrocytes in maintaining neuronal function by offering neurotrophic support we investigated the hypothesis that HBO therapy may exert beneficial effect on acute CO poisoning-induced impairment in intrinsic neurotrophic activity. Exposure to 3000 ppm CO in air followed by 24–72 h of normoxia caused a progressive decline of gene expression, synthesis and secretion of nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3) to different extent. 1 h treatment with 100% oxygen disclosed a pressure- and time-dependent efficacy in preserving astrocytic neurotrophic support. The beneficial effect was most evident when the astrocytes were exposed to HBO 1–5 h after exposure to CO. The results further support an active role of hyperbaric, not normobaric, oxygenation in reducing dysfunction of astrocytes after acute CO poisoning. By preserving endogenous neurotrophic activity HBO therapy might promote neuronal protection and thus prevent the occurrence of late neuropsychological sequelae.